Red Ochre Women: sisters in the struggle for educational reform - McCarthy, Helen; Amagula, J. (Batchelor Press, 2015)
For over thirty years Jacqueline Amagula and Helen McCarthy have been working together with parents and teachers where they have observed and listened as communities often expressed dissatisfaction with the way mainstream non-Indigenous education was delivered in their schools. Together Jacqueline and Helen have maintained a long alliance in their passion to work towards reforming the existing anglo-centric paradigm for learning so that Aboriginal children are taught in culturally sensitive ways. Jacqueline as the past-Chairperson of The Ngakwurralangwa College Advisory Board has made it her life’s work to reform education through this role in educating her people through her teaching and experiences; symbolic in the name Ngakwurralangwa 'Our Way': we own it and we lead it, we have our say and we have the voice. Helen has shared Jacqueline’s struggle documenting this long-term commitment of wanting to craft ways of learning, different to those espoused by mainstream government Departments of Education for the teaching of young Aboriginal learners as the underpinning story of her PhD dissertation. Exposing some of the realities of the impact of what happens in communities when Government intervention directives determine programs are to be abolished or when highly effective learning centres are shut down. They want to share their story and tell the history of this long-term struggle for educational reform and how as allies they continue to seek ways to improve educational experiences for Aboriginal learners. Key words: Allies, Both-ways/Two Way learning, Transformatory Education,